2014
DOI: 10.18632/oncotarget.1943
|View full text |Cite
|
Sign up to set email alerts
|

Multigene mutational profiling of cholangiocarcinomas identifies actionable molecular subgroups

Abstract: One-hundred-fifty-three biliary cancers, including 70 intrahepatic cholangiocarcinomas (ICC), 57 extrahepatic cholangiocarcinomas (ECC) and 26 gallbladder carcinomas (GBC) were assessed for mutations in 56 genes using multigene next-generation sequencing. Expression of EGFR and mTOR pathway genes was investigated by immunohistochemistry. At least one mutated gene was observed in 118/153 (77%) cancers. The genes most frequently involved were KRAS (28%), TP53 (18%), ARID1A (12%), IDH1/2 (9%), PBRM1 (9%), BAP1 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 46 publications
(52 reference statements)
12
161
4
1
Order By: Relevance
“…4, Supplementary Table 5). Somatic substitutions were predominantly C:G4T:A transitions as previously reported in iCCA and other cancers [7][8][9][10][11] . Of the mutations identified, 64% were missense, 28% were silent, 5% were nonsense and 3% were indels (Fig.…”
Section: T C a C A A C C A A T G A G -G A T G G C T A C A A T A G T Csupporting
confidence: 79%
See 3 more Smart Citations
“…4, Supplementary Table 5). Somatic substitutions were predominantly C:G4T:A transitions as previously reported in iCCA and other cancers [7][8][9][10][11] . Of the mutations identified, 64% were missense, 28% were silent, 5% were nonsense and 3% were indels (Fig.…”
Section: T C a C A A C C A A T G A G -G A T G G C T A C A A T A G T Csupporting
confidence: 79%
“…Novel mutations in chromatin remodelling genes (for example, ARID1A, BAP1 and PBMR1) have emerged and account for the most frequent mutations reported so far in iCCA (B25%) 8,9 as it has also been corroborated in recent studies where mutations in such genes have been identified even at higher frequency (34-46%) 10,20 . At the same time, already described mutations (for example, KRAS, IDH1/2, and EGFR) have been confirmed [7][8][9][10][11]20 . Notably, IDH1/ 2-activating mutations occur in B20% of the iCCA cases 4 -17% in our series-and tend to be mutually exclusive with other mutations.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This distribution suggests that biologically relevant mutations are selected for in vivo. The high incidence of Pten mutations can indeed be explained by the key importance of PI3K signaling in hepatobiliary tumorigenesis in humans and mice (32)(33)(34). Likewise, the lack of Brca1/2 mutations reflects their extremely rare alteration in human ICC/HCC (SI Appendix, Table S1).…”
Section: Quantitative Analysis Of Target Site Mutations In Healthy LImentioning
confidence: 99%